MODEL OF BALANCE OF ENERGY RESOURCES OF THE COUNTRIES OF EURASIA - T. A. Stanbekov (Финансы: теория и практика, 2017)
Relevance of a subject of research it is caused by not rather high level of coordination of development of an oil and gas complex of the countries of Eurasia. The balance of energy resources of the countries of Eurasia is characterized by existence, on the one hand, of the countries with a high potential of hydrocarbons, with another, the countries with the low level of existence of energy resources. The purpose of article is development of model of balance of energy resources of the countries of Eurasia. Methods of research were the functional analysis, a method of induction and deduction. The review of a condition of tendencies of development of the energy market of the countries of Eurasia is presented in article. The role of supply of hydrocarbons in a format of integration of the countries of Eurasia and decrease in product cost is noted. The analysis of a condition of production of natural gas and oil of CIS countries is carried out. The model of balance of energy resources of the countries of Eurasia taking into account current trends is offered. The model will allow to optimize deliveries of energy resources of the countries of Eurasia.